Oral pathology : clinical pathologic correlations - Regezi, Joseph A.; Sciubba, James J.; Jordan, Richard C. K. (St. Louis, Mo. : Saunders/Elsevier, 2008)
This fifth edition provides a comprehensive and visually oriented approach to understanding oral diseases. It emphasizes the correlation between clinical presentation, radiographic features, and microscopic pathology. Organized by the way a clinician encounters lesions, the text covers a wide range of conditions from common mucosal diseases to complex odontogenic tumors. It features hundreds of high-quality color illustrations and photomicrographs, along with updated treatment protocols, making it an essential reference for dental students and practitioners.
Title from CD-ROM label: Oral pathology image bank.
Includes bibliographical references and index.
System requirements for accompanying CD-ROM: IBM PC or compatible ; Windows 2000 or XP ; 64 MB RAM ; Internet Explorer 5.0 or later.
Keywords: Mouth -- Diseases; Stomatognathic system -- Pathology; CD-ROMs -- Catalogs